Sistem Pencatatan Dan Pelaporan Surveilans Infeksi Nosokomial Di RS Premier Surabaya - Janah, Miftakhul; Martini, Santi; Notobroto, Hari Basuki (Universitas Muhammadiyah Sidaorjo, 2023)
Nosocomial infection is infection that occur in patients who are hospitalized. One of infection control programs is the surveillance activities. Refer to the Instructions Practical Hospital nosocomial infections Surveillance by the Ministry of health (2011) that computer usage in surveillance activities will help increase the efficiency of data collection and analysis. The propuse of this study is to develop recording and reporting nosocomial infection surveillance system. Methods: this study type is action research with system development life cycle (SDLC) methods , the stages of SDLC is planning, analysis, design, implementation and usage. The instruments used in this study by creating an DFD,ERD, data dictionary and continued with the development of applications using PHP and mySQL. Data collection through interviews and observations. The study results in the form of web-based applications further tested using the method of Technology Accepatnce Mode (TAM). Keyword: Nosocomial infection surveillance, recording and reporting, system development, rs premier surabaya